Removable orthodontic appliance for extrusion of single upper anterior tooth and crowding lower anterior in adult: a case report - Zenia A. Utomo; Sri Suparwitri (Journal of Dentomaxillofacial Science, 2020)
Objective: Supra-eruption maxillary incisor is a usual case that finding in dental practice. Over eruption of such tooth and crowding can lead for traumatic occlusion and functional disturbance. This case report presented patient 26-year-old female class I malocclusion with supra-eruption right central incisor maxillary caused of traumatic and anterior mandibular mild crowding. Methods: This treatment option indicated for orthodontic removable appliance due to small discrepancy. Interproximal enamel reduction as an alternative to solve the problem of mandibular negative space discrepancy. The simple modification in removable orthodontic appliance used with glass ionomer cement on labial surface of right central incisor maxillary. Malposition of lower teeth was corrected with modification of the Hawley appliance consisting of labial arch, adam clasp, and simple spring.Results: After 5 months 14 days treatment, supra-eruption right central incisor maxillary has corrected usage of removable orthodontic appliance with glass ionomer cement on labial surface. Anterior mandibular mild crowding has corrected with removable appliance. Conclusion: Successful orthodontic results with this treatment option will achieve by a careful diagnosis, establish with the aid of a diagnostic setup, professional skills, and patient cooperative.